Extracellular vesicles impose quiescence on residual hematopoietic stem cells in the leukemic niche - Abdelhamed, Sherif (EMBO Rep, 2019)
Progressive remodeling of the bone marrow microenvironment is recognized as an integral aspect of leukemogenesis. Expanding acute myeloid leukemia (AML) clones not only alter stroma composition, but also actively constrain hematopoiesis, representing a significant source of patient morbidity and mortality. Recent studies revealed the surprising resistance of long‐term hematopoietic stem cells (LT‐HSC) to elimination from the leukemic niche. Here, we examine the fate and function of residual LT‐HSC in the BM of murine xenografts with emphasis on the role of AML‐derived extracellular vesicles (EV). AML‐EV rapidly enter HSC, and their trafficking elicits protein synthesis suppression and LT‐HSC quiescence. Mechanistically, AML‐EV transfer a panel of miRNA, including miR‐1246, that target the mTOR subunit Raptor, causing ribosomal protein S6 hypo‐phosphorylation, which in turn impairs protein synthesis in LT‐HSC. While HSC functionally recover from quiescence upon transplantation to an AML‐naive environment, they maintain relative gains in repopulation capacity. These phenotypic changes are accompanied by DNA double‐strand breaks and evidence of a sustained DNA‐damage response. In sum, AML‐EV contribute to niche‐dependent, reversible quiescence and elicit persisting DNA damage in LT‐HSC.